Large trees establish more rapidly when transplanted bare root. Issue 2 (2nd April 2020) - Watson, Gary; Hewitt, Angela
ABSTRACT: Large trees have been transplanted bare root for centuries, and the method is again being used more frequently as air excavation tools have reduced the labour required. The diameter of the woody root system moved with a bare root tree can be more than twice that of a standard soil ball, representing as much as five times the amount of root system. Roots lost when the tree is dug must be replaced before a transplanted tree can be considered established in its new location. Moving such a large portion of the woody root system makes establishment more dependent on replacement of the fine roots, rather than replacing the spread of the woody root system, which can take many years for large trees. With establishment dependent primarily on fine root replacement, which can take place in the first season, growth of white spruce ( Picea glauca ), London plane ( Platanus x acerifolia ), lacebark elm ( Ulmus parvifolia ) and zelcova ( Zelcova serrata ), ranging from 13 to 28 cm average DBH, all returned to normal, or greater, in the second season after transplanting, regardless of size. Using this method requires considerable experience, and may be more costly, but it may be a viable option for some situations.